Effect of Dielectric Barrier Discharge on the Airflow Around a Cylinder - Droubi,Ashraf El (2012)
Abstract: Fluids in a dielectric barrier glow discharge at atmospheric pressure have attracted interest from communities of thermo and fluid dynamics, as well as control. This work investigated the effects of a plasma actuator, operating at 8.0 kV and 4.4 kHz, on the pressure distribution around a polyvinyl chloride circular cylinder in low-velocity airflow. The experiment was repeated with the actuator at various angles. The results show an acceleration of the flow demonstrated by a 60% lower pressure coefficient at the actuator area. The flow separation was also delayed by an angle of as much as 30°. These effects were shown to be greater when the actuator was positioned at an angle closer to the separation area.